Effect of Garlic (Allium sativum L.) Supplemented Feed on Survival and Growth of Common Carp (Cyprinus carpio L.) - Muzaffar, Farwah; Ansal, Meera D.; Dhawan, Asha (Indian Journal of Animal Nutrition, 2017)
Garlic (Allium sativum L.) powder was supplemented in the feed @ 0, 1, 2 and 3% level (0, 10,20 and 30 g/kg feed) of common carp (Cyprinus carpio L.) to evaluate its growth promoting efficacy. The studywas carried out in outdoor cemented tanks (80 m2), where common carp fry stocked @ 10000/ha, were fed with control and garlic powder supplemented feeds for 120 days @ 5% of BW during first 45 days and @ 2% BW during last 75 days. Garlic supplementation @ 1, 2 and 3% did not affect water quality, nutrient status and plankton production in any of the garlic fed groups. Although, feed cost increased with increase in garlic supplementation rate but a higher (P<0.05) fish growth was recorded with all the garlic supplemented feeds.The net weight gains and specific growth rates were higher with 2% garlic supplemented feed. Garlic supplementation in fish feed did not affect fish survival up to 2% incorporation level but a considerable decline was observed at 3% inclusion level. Garlic supplementation @ 1 and 2% resulted in 39.43 and 93.49% higher fish harvest which not only compensated for the higher feed cost but also resulted into extra earning to the tune of 26.42 and 59.34%, respectively. Therefore, garlic powder could be incorporated up to 2% level in common carp feed for more production with better profitabilty without affecting survival of the fish.